2009
DOI: 10.1021/ja901875v
|View full text |Cite
|
Sign up to set email alerts
|

A New Gadolinium-Based MRI Zinc Sensor

Abstract: The properties of a novel Gd3+-based MRI zinc sensor are reported. Unlike previously reported Gd3+-based MRI contrast agents, this agent (GdL) differs in that the agent alone binds only weakly with human serum albumin (HSA) while the 1:2 GdL:Zn2+ ternary complex binds strongly to HSA resulting in a substantial, three-fold increase in water proton relaxivity. The GdL complex is shown to have a relatively strong binding affinity for Zn2+ (KD = 33.6 nM), similar to the affinity of the Zn2+ ion with HSA alone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
189
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(195 citation statements)
references
References 38 publications
5
189
0
1
Order By: Relevance
“…The 60% fat diet has been shown to induce obesity, glucose intolerance, hyperinsulinemia, and expanded β-cell mass in C57BL/6 mice (25,26). Representative microscopy of islets showed a marked increase in islet diameter in diet-induced obese (DIO) mice vs. 3 ) of pancreatic tissue (regions with enhanced signal intensity by threefold or more summed over 14 separate MRI slices) in the three groups of animals as detected by GdDOTA-diBPEN. The average functional volumes, SDs, and P values are shown above each bar (n = 10 for control 12-wk ; n = 6 for control 24-wk ; n = 6 for DIO 24-wk ).…”
Section: Glucose + Gddota-dibpen (12-wk Old)mentioning
confidence: 92%
See 2 more Smart Citations
“…The 60% fat diet has been shown to induce obesity, glucose intolerance, hyperinsulinemia, and expanded β-cell mass in C57BL/6 mice (25,26). Representative microscopy of islets showed a marked increase in islet diameter in diet-induced obese (DIO) mice vs. 3 ) of pancreatic tissue (regions with enhanced signal intensity by threefold or more summed over 14 separate MRI slices) in the three groups of animals as detected by GdDOTA-diBPEN. The average functional volumes, SDs, and P values are shown above each bar (n = 10 for control 12-wk ; n = 6 for control 24-wk ; n = 6 for DIO 24-wk ).…”
Section: Glucose + Gddota-dibpen (12-wk Old)mentioning
confidence: 92%
“…The mass of pancreatic β-cells in humans generally increases throughout adult life (1), whereas the functional sensitivity of β-cells to high glucose tends to decline with age (2) and can be reduced significantly before type 2 diabetes is diagnosed clinically (1,2). We show here that divalent zinc ions (Zn 2+ ), coreleased with insulin from β-cells in response to high glucose, are readily detected by MRI using the Zn 2+ -responsive T 1 agent GdDOTA-diBPEN (3). Previous studies have shown that the Zn 2+ concentration in the extracellular space of islets approaches 475 μM during glucose-stimulated insulin secretion (GSIS) (4), well above the detection limit of GdDOTA-biBPEN.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Among these, O-(1H-benzotriazol-1-yl)-N,N,N 0 ,N 0 -bis-(tetramethylene) uronium hexafluoro phosphate (HBTU) is the most attractive reagent based upon cost and availability. The latter was further supported by the fact that we were able to prepare in good yield a DOTA-bisamide derivative by coupling DOTA-bis-tert-butyl ester (15) to the proper amine intermediate using HBTU in DMF (16). However, under the same coupling conditions but using acetonitrile as the solvent, the product was obtained in low yield (unpublished results).…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, several Zn 2ϩ -sensitive MRI contrast agents have recently been reported. [30][31][32] Secondly, another possible approach for the development of responsive MRI contrast agents is the RIME (receptor-induced magnetization enhancement) approach. [33][34][35] The binding of a MRI contrast agent to a macromolecule substantially slows molecular rotation of the Gd 3ϩ complex, resulting in an additional increase in the r 1 relaxivity through the rotational correlation time t R .…”
mentioning
confidence: 99%